2017
DOI: 10.3892/mco.2017.1412
|View full text |Cite
|
Sign up to set email alerts
|

Role of Krüppel-like factor 4 and heat shock protein 27 in cancer of the larynx

Abstract: Abstract. Late detection and lack of standard treatment strategies in larynx cancer patients result in high levels of mortality and poor prognosis. Prognostic stratification of larynx cancer patients based on molecular prognostic tumor biomarkers may lead to more efficient clinical management. Krüppel-like factor 4 (KLF4) and Heat Shock Protein 27 (HSP27) have an important role in tumorigenesis and are considered promising candidate biomarkers for various types of cancer. However, their role in larynx carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In particular, a study carried out on 50 samples of LSCC reported a correlation between the cytoplasmatic expression of phosphorylated HSP27 and nuclear expression of both phosphorylated and non-phosphorylated HSP27 and neck node metastases [31]. Moreover, the expression level of HSP27 is found to be related to tumor stage (p-value 0.0039) and grade of differentiation (p-value < 0.001) [29]. A 2007 study found that overexpression of this protein in LSCC induces chemoresistance against cisplatin without effects against RT.…”
Section: Hsp27mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a study carried out on 50 samples of LSCC reported a correlation between the cytoplasmatic expression of phosphorylated HSP27 and nuclear expression of both phosphorylated and non-phosphorylated HSP27 and neck node metastases [31]. Moreover, the expression level of HSP27 is found to be related to tumor stage (p-value 0.0039) and grade of differentiation (p-value < 0.001) [29]. A 2007 study found that overexpression of this protein in LSCC induces chemoresistance against cisplatin without effects against RT.…”
Section: Hsp27mentioning
confidence: 99%
“…Studies found that their overexpression and their role in carcinogenesis depend on the type of cancer [26,27]. For instance, HSP27 overexpression in breast, liver, and prostate cancers is related to poor prognosis, whereas its high expression in esophageal and lung squamous cell carcinoma is related to good prognosis [26,28,29].…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%
“…KLF 4 can regulate multiple important biological processes such as neuroinflammation, oxidative stress, proliferation, differentiation, and apoptosis ( Kaushik et al, 2010 ; Mamonkin et al, 2013 ; Zhang et al, 2015 ; Miao et al, 2017 ; Xu et al, 2017 ). Amounts of previous studies focused on KLF 4 ’s role in cancer development and progression ( Karam et al, 2017 ; Yadav et al, 2018 ). KLF 4 is a dual-function transcription factor, which can exert its role as an oncogene or a tumor suppressor gene depending on the cancer type or cancer stage ( Evans and Liu, 2008 ).…”
Section: Introductionmentioning
confidence: 99%